Needs Analysis of English Learning Skills for Students of Hospitality Study Program - Makmun Syaifudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Needs analysis plays a significant part in the construction of an English language curriculum that is tailored to learning needs. Students' descriptions of their needs, weaknesses, and desires constitute important factors that English teachers must consider before establishing appropriate lesson plans and teaching and learning resources. This study was designed with a descriptive qualitative research model. Data was collected through questionnaires and interviews. This data collection method involved all students from the Politeknik Indonusa Surakarta for Hospitality program in their first semester of Academic Year 2023, with a total of 93 students participated. The questions were provided online using Google form. When completing the questionnaire, respondents are given the choice from a number of different responses. Based to the results of the Needs Analysis on English subject, the main objective of Hospitality Study Program students learning English is to help them develop in their jobs in the service and hospitality industries. Students emphasized the importance of learning speaking skills, despite the fact that other language skills are equally important to improve. Each need to master aspects of English language skills, on the other hand, must be in line with their professional career development. This study has implications for fulfilling learning requirements in the hospitality study program as a guide to developing English teaching materials for students in the program. Keywords: ESP, hospitality Study Program; Needs Analysis, English Language Skills